Anwar Ibrahim : dari Cherok To' Kun ke Kuala Kangsar - Amin Ahmad, 1982- (Kuala Lumpur : ILHAM Books, 2021)
Biography of Dato' Seri Anwar Ibrahim, a politician and 10th Prime Minister of Malaysia.
Includes bibliographical references (pages 141-150).
Keywords: Anwar Ibrahim, -- 1947-.; Politicians -- Malaysia -- Biography; Political leadership